A study of transition from periodic dripping to jetting in the presence of an electric field. (October 2021) - Wang, Zhentao; Yang, Shiqi; Zhang, Yaosheng; Li, Bin
Highlights: The necking time is independent of electric field in a reasonable range of flow rate. The transition from dripping to jetting is enhanced by electric field for relatively small tube. A model for the transition from periodic dripping to jetting is established in an electric field. A critical criterion for the transition is presented and in reasonable agreement with experiments. Abstract: A liquid is issued from the outlet of the capillary tube vertically, and drop formation may be in the form of periodic dripping, dripping faucet and jetting, which usually depends on flow rate or Weber number. We consider the critical Weber number ( W eC = ρV 0 2 D / σ ) at which the transition from periodic dripping to jetting occurs in the presence of an electric field, where high-resolution images are recorded. The necking time is mainly related to nozzle diameter and surface tension, and independent of electric potential and flow rate (in a reasonable range).The first threshold limit decreases with an increase in electric potential, where the dripping faucet is clearly affected and the point of drop detachment gradually increases. When the drop formation is in the form of dripping faucet, the transition from dripping faucet to jetting regime is enhanced by electric potential, where a sudden transition could be observed in an extremely limited range of liquid flow rate. The critical criterion (Weber number) is presented to determine the transition from dripping to jetting in the presence of an electric field. The critical Weber number is in a reasonable agreement with the experiment, although the predicted results are quantitatively divergent with experimental data.